(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article, based on scientific opinions, covers in detail the thematic groups of the lexical-semantic group of names of food products in the Uzbek language, and also analyzes the assimilation of new food products that enrich these thematic groups. Thematic groups of names of new food products emerging in gastronomic discourse are also discussed.